Visual Evoked Potentials of the Retina and Visual Cortex after a Prolonged Exposure to the Radiation of LED Fixtures with Variable Spectral Energy Characteristics - V. V. Neroev; I. B. Ushakov; M. V. Zueva; O. M. Manko; E. P. Lantukh; I. V. Tsapenko; A. E. Smoleevsky; G. A. Nazarova (Российский офтальмологический журнал)
The paper’s objective was to determine the nature of changes in the bioelectric activity of the retina and the visual cortex in conditions of long-term staying of man in an enclosed space with artificial light generated by light-emitting diode (LED) lamps with variable spectral and power characteristics. In addition to a set of standard ophthalmic examinations, we recorded electroretinograms (ERG) to diffuse flashes, pattern-reversing and multifocal stimuli, and visual evoked cortical potentials (VEP) using the diagnostic system RETIport/scan21. The examinations were carried out in four healthy volunteers before and after an 11-day hermetic-chamber experiment simulating conditions of the spacecraft. Prolonged exposure to closed LED lighting created by sources with a high correlated color temperature (CCT), was shown to have no pronounced negative impact on the function of the retina. Changes in the amplitude of the ERG and VEP were minor, but displayed certain features specified by the history of previous injuries or functional disorders. Also, according to VEP waveforms to reversing checkerboard pattern, a characteristic sign of changes in the activity of the visual system in all participants was a splitting of the P100 peak, possibly related to temporal uncoupling of the activity of various visual channels. Thus, artificial LED lighting with high CCT can have both positive and adverse effects on the functional activity of the retina and the visual cortex, the nature of which, apparently, depends on the initial functional state of the visual system // Russian Ophthalmological Journal, 2016; 1: 48-55.